Deformation processes of additively manufactured interstitial-strengthened high entropy alloy - Zhang, Wei (2023)
WZ acknowledges the China Scholarship Council for her PhD grant (CSC NO. 201906250212 ). YP acknowledges financial support by Samenwerkingsverband Noord-Nederland (SNN) within the program “3D Print Kompas”. JPO and JS acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES) for its financial support via the project UID/00667/2020 (UNIDEMI). JS acknowledges the China Scholarship Council for her PhD grant (CSC NO. 201808320394 ). The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. SF acknowledges financial support by the National Natural Science Foundation of China (No. 52105318 ) and Fundamental Research Funds for the Central Universities (Youth Teacher International Exchange & Growth Program No. QNXM20220027 ). Publisher Copyright: © 2023 The Authors